Zeely - Hamilton, Virginia 1936-2002 (Aladdin Books Macmillan Publishing, 1987)
Geeder's summer at her uncle's farm is made special because of her friendship with a very tall, composed woman who raises hogs and who closely resembles the magazine photograph of a Watutsi queen.